اتجاهات الطلبة نحو الممارسة الارطفونيا دراسة ميدانية لعينة من طلبة الارطفونيا في جامعة الاغواط - ابتسام ديدي; أمال دمانة; بن يطو جلول (My University, 2020)
The current study aims to try to reveal the nature of the trends of Artofunia students towards Artofunia، in which we relied on the descriptive curriculum. The two study lists used a questionnaire on the trends of students towards Artofunia، which was prepared by both، and applied to a sample of 82 students studying Arvania (second and third years) and specialized in language and communication diseases (first year، second year، master) at University of Lamecar) The registrars of the 2019-2020 school year. The results of the study have a number of results، the most important of which are : - The student's sample attitudes towards the practice of Arodonism are positive . - The student trends in the sample study towards the university formation in Artovonia are positive . - The student's sample trends towards the Aromatic Specialist's profession are positive at the level of 0.01، because the arithmetic mean of 15.0244 is greater than the theoretical average of 14، so the hypothesis is achieved. The trend among students towards the professional profession is positive، according to the two lists، and the large number of private clinics in the current period is higher than in previous years Student trends، Artovonia practice، university formation